ANALYSIS OF THE ASSET BASED COMMUNITY DEVELOPMENT (ABCD) MODEL FOR ANGKRINGAN 5.0 - WIJI LESTARI; HERLIYANI HASANAH; RUDI SUSANTO (CV KULTURA DIGITAL MEDIA, 2022)
The study aims to apply the Asset Based Community Development (ABCD) method for the development of angkringan into the angkringan 5.0 model. The method used is to use the stages in ABCD, namely are inculturation, discovery, design, define and reflection. Collecting data using literature study, observation and questionnaires. The results of the ABCD method analysis can provide an illustration that angkringan assets play an important role in business development.